Two new species of Pelargonium (Geraniaceae) from the Western and Northern Cape Provinces (South Africa) and their position within P. section Hoarea - Marais, Elizabeth M.; Le Roux, Anso (Phytotaxa, 2021)
Pelargonium hammansbergense and P. roseopetalum are described as new species. Both are deciduous geophytes with turnip-shaped tubers belonging to P. section Hoarea. These two species share spathulate petals with narrow cuneate claws.  However, they differ in leaf shape, flower colour and markings on the petals. Their flower structure corresponds to that of P. aridicola, P. hirtipetalum, P. pubipetalum, P. reflexipetalum and P. tripalmatum. The seven species are compared with regard to the flower and leaf morphology, palynology and chromosome numbers. They all occur in the winter rainfall region along the west coast of South Africa. The two new species described here are illustrated and a key for the identification of the seven species with a P. aridicola flower type is included.